A high incidence of non-cavity nesting in an introduced population of House Sparrows suggests that the species should not be constrained by cavity-nest site availability - Elizabeth Louise Sheldon; Simon Charles Griffith (Avian Research, 2017)
Abstract Background The House Sparrow (Passer domesticus) has undergone dramatic population declines in many parts of Europe. It has been widely hypothesised that a lack of cavity nest sites has contributed to this decline. However the idea of the House Sparrow being nest site limited is somewhat incompatible with the long history of nest site plasticity in the species. Methods The nest-site selection in a population of non-native House Sparrows introduced to Australia from Europe just over 150 years ago was characterised. The prevalence of non-cavity nesting was quantified, and nest-site selection in terms of landscape and nesting structure were described. Results Flexible nesting behaviors were reported over a range of different landscapes and a surprisingly high rate of nesting in vegetation (43%) was documented. Most nests found in vegetation were not in cavities, but were woven into the foliage and supported by branches and stems. Conclusion The high rate of vegetation nesting indicates that in this introduced population, the House Sparrow is unlikely to be constrained by cavity-nest site availability. The high degree of nest site plasticity in the Australian population may suggest that European House Sparrows have the potential to shift away from their proclivity for cavity nests. Future work in Europe should examine the incidence of non-cavity nesting in House Sparrows more closely, and perhaps reconsider the idea that House Sparrows are nest-site constrained.